An exploration of key issues and potential solutions that impact physician wellbeing and professional fulfillment at an academic center - Iris Schrijver; Keri J.S. Brady; Mickey Trockel (PeerJ, 2016)
Background. Physician wellness is a vital element of a well-functioning health care system. Not only is physician wellness empirically associated with quality and patient outcomes, but its ramifications span individual, interpersonal, organizational, and societal levels. The purpose of this study was to explore academic physicians’ perceptions about their work-related wellness, including the following questions: (a) What are the workplace barriers and facilitators to their wellness? (b) What workplace solutions do theythinkwouldimprove their wellness? (c)What motivates their work? and (d) What existing wellness programs are they aware of? Methods. A multi-method design was applied to conduct a total of 19 focus group sessions in 17 clinical departments. All academic faculty ranks and career lines were represented in the 64 participating physicians, who began the sessions with five open-ended survey questions pertaining to physician wellness in their work environment. Participants entered their answers into a web-based survey program that enabled anonymous data collection. The initial survey component was followed by semi-structured focus group discussion. Data analysis of this qualitative study was informed by the general inductive approach as well as a review of extant literature through September 2015 on physician wellness, professional fulfillment, satisfaction, dissatisfaction, burnout and work-life. Results. Factors intrinsic to the work of physicians dominated the expressed reasons for work motivation. These factors all related to the theme of overall contribution, with categories of meaningful work, patient care, teaching, scientific discovery, self-motivation and matching of career interests. Extrinsic factors such as perceptions of suboptimal goal alignment, inadequate support, restricted autonomy, lack of appreciation, and suboptimal compensation and benefits dominated the risk of professional dissatisfaction. Discussion. Our findings indicate that the factors that enhance professional fulfillment and those that precipitate burnout are distinct: motivation and quality of work performed were supported by domains intrinsic to the work itself, whereas external dysfunctional work aspects resulted in frustration. Thus, it can be anticipated that optimization of physician wellness would require tailored approaches in each of these dimensions with sustained funding and support for wellness initiatives. Physicians identified the availability of resources to enable them to thrive and provide excellent patient care as their most important wellness-enhancing factor.